Promoting student success in online post-graduate studies at a South African University: The role of professional and administrative support - Johannes, E.; Lalendle, L. (South African Journal of Higher Education, 2024)
Post-graduate online students studying in cohorts are expected to collaborate effectively with their peers and instructors in the virtual environment and are presumed to have the necessary skills needed for self-directed online learning. However, studies have shown that the low retention and success rates in online learning could be attributed to individual students experiencing a sense of isolation in a community of online students. Providing various non-academic support is as crucial for ensuring success as academic support services. More importantly, the support should acknowledge and address the unique set of skills, experiences, and expectations of the individual student in the community of online learners. This study aimed to ascertain whether professional and administrative student support that focused on the individual needs of the post-graduate student promotes retention and success in online studies. A qualitative case study at a business school at a South African higher education institution evaluated the professional and administrative support types, range and timing in promoting success in online post-graduate studies. This included the content analysis of key documents such as the self-evaluation report and the survey report on evaluation, impact and lifelong learning of a post-graduate qualification, followed by a focus-group session to ascertain staff perceptions of the professional and administrative services and resources in promoting success in online post-graduate studies. Using Simpson’s Proactive Motivational Support model (PaMS) as a lens, the study revealed a lack of motivational aspects of student support for online post-graduate students. Furthermore, the results affirmed the presumption of post-graduate students as a homogenous group prepared to succeed in online learning communities. Moreover, that limited provision was made to support online post-graduate students from remote areas and for those with disabilities. The study concludes that a more personalised approach to student support will motivate post-graduate students to become successful self-directed students in a community of online learners. Moreover, a focused school, college and institutional approach and an integrated inter- and intra-institutional collaboration are needed to enhance self-directed learning, foster a sense of belonging, and promote success in online post-graduate studies.